A method for the extraction of high quality fungal RNA suitable for RNA-seq - Cortés-Maldonado, Leyda; Marcial-Quino, Jaime; Gómez-Manzo, Saúl; Fierro, Francisco; Tomasini, Araceli (Journal of microbiological methods, 2020)
Transcriptomic analysis is an OMICs technology that is becoming indispensable to understand and get a complete picture of cell functioning and adaptation to the environmental cues the cell is continuously receiving. Among the techniques available to perform transcriptomics, RNA-seq is becoming the method of choice. The quality of the RNA used for the generation of cDNA libraries and subsequent sequencing is crucial for the success of the process. Good RNA-seq performance is often limited by problems such as low RNA yield and/or integrity, RNA stability, and contamination with DNA, salts or chemicals. RNA isolation from fungi usually faces these problems and is particularly sensitive to degradation due to the high RNase activity content present in many species. Here we describe the development of a robust, highly reproducible and simple RNA purification method for filamentous fungi, which combines various strategies to get fully DNA-free RNA samples of high purity and integrity without the need to use a DNase I digestion step. The obtained RNA samples complied with all required standards to be used for RNA-seq and showed an excellent performance when subjected to Illumina-HiSeq 2500. •Development of a de novo protocol for RNA extraction in filamentous fungi.•The protocol is robust, reproducible and eliminates all traces of contaminant DNA.•The RNA shows higher yield, purity and integrity than the RNA extracted with other methods.•The quality of the RNA obtained with the protocol implemented in this work was validated by RNA-seq.•Proposed for RNA isolation in filamentous fungi for which no protocols are available.